2015
DOI: 10.1108/jsma-08-2014-0069
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of relational factors: Sino-foreign joint venture partnering

Abstract: Purpose -Despite recent threats of economic contraction, China still offers attractive opportunities for foreign companies seeking to expand their business activities through joint venturing (JV) partnering entry strategies. Recent research has indicated a growing recognition of the importance of relational factors in JV partnering. The purpose of this paper is to build on recent research findings that identify critical relation success factors in JVs and explores these in the context of a Hong Kong-based civi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(32 reference statements)
2
3
0
Order By: Relevance
“…In the empirical research, we showed that process innovation, together with organizational innovation, management innovation, and human resources innovation, create social and business value. As explained in the literature, we confirm the importance of implementing innovation management that merges various types of innovation rather than merely optimising each kind of innovation separately ( O’Regan and Ghobadian, 2004 ; Lau and Tovstiga, 2015 ).…”
Section: Discussionsupporting
confidence: 83%
“…In the empirical research, we showed that process innovation, together with organizational innovation, management innovation, and human resources innovation, create social and business value. As explained in the literature, we confirm the importance of implementing innovation management that merges various types of innovation rather than merely optimising each kind of innovation separately ( O’Regan and Ghobadian, 2004 ; Lau and Tovstiga, 2015 ).…”
Section: Discussionsupporting
confidence: 83%
“…In the empirical research, we show that process innovation, together with organisational innovation, management innovation and human resources innovation, create social and business value. As explained in the literature, we confirm the importance of implementing innovation management that merges the various types of innovation rather than merely optimising each kind of innovation separately (O' Regan and Ghobadian 2004;Lau and Tovstiga 2015). Designing new products and/or services stemming from innovation management offers new market opportunities that are beneficial for both the firm as well as for society, thereby generating CSV (Corazza et al 2017;Obsuwan et al (2021).…”
Section: Practical and Managerial Implicationssupporting
confidence: 77%
“…This eliminated international JVs, domestic JVs with more than two partners, and JVs with private firms. Our findings may also differ if they were studied in countries other than the US: for example, the success of a JV in China may be greatly influenced by culturally-based relational factors (Lau and Tovstiga, 2015) Furthermore, the sole use of S&P 500 firms is a limitation, as our results may not be generalizable to firms of smaller size.…”
Section: Discussionmentioning
confidence: 66%